Du terrain au Tour du monde : la fabrique du lointain - Victoire Lallouette (Les Cahiers de l'École du Louvre)
It is amusing to observe that the misappropriation of images, which has become so obvious and omnipresent in our daily lives, has a long history; it may be found from early twentieth century when one takes a look at the publications of the French illustrated press recounting the narratives of an explorer of New Guinea. It is the story of Marquis de Cacqueray de Lorme, a bourgeois heir, who set off in 1895 to find the few French Catholic missionaries in New Guinea, the vast island largely unknown to Westerners.